2006
DOI: 10.1103/physrevb.73.235424
|View full text |Cite
|
Sign up to set email alerts
|

Spin-polarized field emission from Ni(001) and Ni(111) surfaces

Abstract: Results are presented of a first-principles calculation of the spin-polarized field emission from ferromagnetic Ni͑111͒ and Ni͑001͒ surfaces. The electronic structure of both surfaces exposed to an external field is determined by combining the surface-embedded Green function approach and the full-potential linearized augmented plane-wave ͑FLAPW͒ method within the local spin density approximation. We discuss the contributions of different states to the field-emission current. In particular, we show that delocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 45 publications
3
27
0
Order By: Relevance
“…11 More recent theoretical works have also predicted two SSs, which are separated by 180-350 meV. [14][15][16][17] Early ARPES measurements of Ni͑111͒ using lasers revealed two parabolic surface states with upward and downward dispersions at the ⌫ point of the surface Brillouin zone ͑SBZ͒. 13 The spin-split Shockley SSs above E F were studied by the spin-resolved inverse photoemission spectroscopy ͑IPES͒.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…11 More recent theoretical works have also predicted two SSs, which are separated by 180-350 meV. [14][15][16][17] Early ARPES measurements of Ni͑111͒ using lasers revealed two parabolic surface states with upward and downward dispersions at the ⌫ point of the surface Brillouin zone ͑SBZ͒. 13 The spin-split Shockley SSs above E F were studied by the spin-resolved inverse photoemission spectroscopy ͑IPES͒.…”
Section: Introductionmentioning
confidence: 98%
“…[10][11][12][13][14][15][16][17][18] The exchange-split Shockley surface states were first predicted by a one-step model photoemission calculation. 11 More recent theoretical works have also predicted two SSs, which are separated by 180-350 meV.…”
Section: Introductionmentioning
confidence: 99%
“…S 2 , on the other hand, is slightly further away from the Fermi energy and shows a hole-like (downward) dispersion (minimum binding energy ∼250 meV). Recent theoretical work [13][14][15] have shown that both surface states are spin split into two components. In the case of S 1 , only the majority component (the one with the highest binding energy) shows a significant contribution to the electronic spectral weight at the Γ point.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, recent first principle calculations have an ability of depicting a physical phenomenon more precisely. As the result, it is predicted that the spin polarization of field emitted electrons from Ni(001) depends on applied electric field, which results from the contribution of a surface state to emission current [4]. However, there are no experimental reports so far on field-dependence of spin polarization of field-emitted electrons.…”
Section: Introductionmentioning
confidence: 94%